Normalizing time in terms of space: What drives the fate of spring thaw-released nitrogen in a sloping Arctic landscape?. (December 2022) - Rasmussen, Laura Helene; Mortensen, Louise H.; Ambus, Per; Michelsen, Anders; Elberling, Bo
Abstract: In the Arctic tundra, snowmelt is followed by soil thaw allowing water and dissolved nutrients to move downslope. However, the fate of the released nitrogen (N) remains unclear, which includes the fraction of N that is lost to downslope transport or converted to N gasses. We have quantified the release of NO3 − into the soil solution and the loss of gaseous N upon thaw and up to a month after first thaw in an Arctic hillslope in W Greenland. We further investigated which factors of the slope ecosystem that influence the NO3 − concentrations and N2 O fluxes throughout two snowmelt and growing seasons using a Structural Equation Model (SEM) linking physical, biological and biogeochemical characteristics across the slope. Snowmelt controls growing season onset, but varies in the landscape. To account for this, we normalized the spatiotemporal variation in snowmelt and soil thaw by measuring NO3 − release and N2 O loss in a controlled laboratory thaw experiment with topsoil cores from along the slope. We furthermore normalized seasonal progression of ecosystem variables in space based on the first day of soil thaw in the field. We tested the variable Day After Soil Thaw (DAST) as the temporal driver in our SEM, and found that season progression is the most important factor to describe patterns in NO3 − concentrations and N2 O fluxes. We conclude that DAST is a useful tool for analysing seasonal patterns in a spatially heterogeneous snowmelt landscape and between different snowmelt years. When normalizing based on first day of soil thaw, we saw that the decreasing NO3 − content over the season did not control the increasing N2 O emissions. Rather, nitrification replaced denitrification as the main N2 O -source during the growing season, where soil temperatures increased and soil moisture decreased. The gaseous N loss from the slope during the first month of thaw was minor and amounted to 1% of the annual N deposition. A NO3 − pulse released into solution after 24 h of thaw, when meltwater moves along the slope and connects upslope with downslope ecosystems, thus constituted a "hot moment" for interaction between landscape N pools, but the NO3 − was immobilized by microorganisms or taken up by plants rather than denitrified and did thus not constitute a hot moment for N2 O emissions. Thus, our results regarding what drives the fate of spring-thaw released N in the sloping Arctic landscape highlight the importance of snowmelt timing and the following number of Day After Soil Thaw as a normalizing factor for biogeochemical processes. This provides an analytical concept for reducing spatial and inter-annual variability to understand general seasonal patterns otherwise hidden. Highlights: Spatial variability in snowmelt can confound biogeochemical seasonal patterns. We monitored an Arctic slope during two very different snowmelt and soil thaw years. We introduce the time variable Day After Soil Thaw in a Structural Equation Model. Normalizing to variation in growing season onset unveiled biogeochemical patterns. N2 O emissions increased with season progression while NO3 − availability decreased.